Mrs2p Forms a High Conductance Mg(2+) Selective Channel in Mitochondria - Schindl, Rainer (The Biophysical Society, 2007)
Members of the CorA-Mrs2-Alr1 superfamily of Mg(2+) transporters are ubiquitous among pro- and eukaryotes. The crystal structure of a bacterial CorA protein has recently been solved, but the mode of ion transport of this protein family remained obscure. Using single channel patch clamping we unequivocally show here that the mitochondrial Mrs2 protein forms a Mg(2+)-selective channel of high conductance (155 pS). It has an open probability of ∼60% in the absence of Mg(2+) at the matrix site, which decreases to ∼20% in its presence. With a lower conductance (∼45 pS) the Mrs2 channel is also permeable for Ni(2+), whereas no permeability has been observed for either Ca(2+), Mn(2+), or Co(2+). Mutational changes in key domains of Mrs2p are shown either to abolish its Mg(2+) transport or to change its characteristics toward more open and partly deregulated states. We conclude that Mrs2p forms a high conductance Mg(2+) selective channel that controls Mg(2+) influx into mitochondria by an intrinsic negative feedback mechanism.